Entretien avec Hao Jingfang - Jingfang; Jingfang (MONDE CHINOIS NOUVELLE ASIE, 2022)
This interview conducted in November 2017 with contemporary Chinese author Hao Jingfang (1984) centers on Hao’s writing trajectories, from her early interest in the science-fiction genre to the diversification of the themes that run through her works. In the light of Hao Jingfang’s experiences and feelings, it is possible to get a glimpse into the sociopolitical context of young Chinese science fiction writers born in the 1980s. The interview also covers the various interpretations of her “Folded Beijing” which has won the Hugo Award for Best Novelette in 2015 in its English translation, as well as Hao’s future projects.